Structural and mechanistic basis of proton-coupled metal ion transport in the SLC11/NRAMP family - Ehrnstorfer, Ines A. (Nat Commun, 2017)
Secondary active transporters of the SLC11/NRAMP family catalyse the uptake of iron and manganese into cells. These proteins are highly conserved across all kingdoms of life and thus likely share a common transport mechanism. Here we describe the structural and functional properties of the prokaryotic SLC11 transporter EcoDMT. Its crystal structure reveals a previously unknown outward-facing state of the protein family. In proteoliposomes EcoDMT mediates proton-coupled uptake of manganese at low micromolar concentrations. Mutants of residues in the transition-metal ion-binding site severely affect transport, whereas a mutation of a conserved histidine located near this site results in metal ion transport that appears uncoupled to proton transport. Combined with previous results, our study defines the conformational changes underlying transition-metal ion transport in the SLC11 family and it provides molecular insight to its coupling to protons.